Flow of History, “Gen Z” and Populism - Mishra, Chaitanya (Dhaulagiri Journal of Sociology and Anthropology, 2026)
The basic objective of this article is to examine the birth and rise of “Generation Z” (henceforth Gen Z) in recent world history and in Nepal, and to explore what this rise may imply for national political systems in Nepal and elsewhere. It is argued here that distinctive and “named” generations such as Gen Z are products not of biological (jaivik) reproduction such as those we evoke when we speak of generations (vansa, pusta, etc.) of parents and those of their children and grandchildren. The distinctiveness of such generations is rooted in distinctive social (i.e. economic, political, cultural) and historical periods they were born into and in distinctive social and historical currents they themselves push forward. In particular, such generations are products of a very rapid flow of history. It is this rapid flow that leads to the regime of named generations in the first place. In addition, it is argued that Gen Z and similar other generations are not the same the world over; it is, instead, necessary to locate sets of Gen Zs within specific regions and countries, i.e. within specific social and historical contexts. The world today is one single historical whole inasmuch as it is intricately integrated across all major dimensions of production and exchange. Yet, the world is highly differentiated, uneven and unequal and it is becoming more so. As such, even as the nature and dynamics of the world today does provide an overall framework for analysis, the specificity of the local and the present must be valorized. It is further argued that the rapid shift in social-historical generations is likely to lead to a move away from the older framework of a durable, ideologically-based, cadre-based, “principled” and ordered political party formation to a formation that is much more populist and, therefore, geared to a shorter time frame, principal-leader-based, less long run and ideologically and programmatically flexible. Populist politics in peripheral countries such as Nepal today is also more “manipulable” at the hands of powerful forces inside and outside the country and, increasingly during the last two decades, along the liminal (mainly cyber-borderland) spaces inhabited mostly by young and Gen Z cyber-denizens of specific but anonymous hues and interests. Finally, and in the context of news reports on initiatives on amendment of the existing constitution, a brief conclusion identifies three key provisions that ought to be honored for a better future.